Solar-Powered Electric Vehicles: Comprehensive Review of Technology Advancements, Challenges, and Future Prospects - Oluwapelumi John Oluwalana; Katarzyna Grzesik (Energies, 2025)
This comprehensive review examines the evolution, current state, and future potential of solar-powered electric vehicles (SEVs) and vehicle-integrated photovoltaics (VIPV). This study analyzed 77 relevant scientific papers published up to March 2025, identifying significant advancements in photovoltaic efficiency, lightweight materials, and integration techniques. Although SEVs and VIPV show promising potential for sustainable mobility, challenges remain in areas such as energy yield optimization, climate adaptability, and economic viability. This review highlights research gaps and proposes future directions, emphasizing the need for standardized testing protocols, improved energy management systems, and innovative material solutions to address these challenges. Key findings include the development of SEVs from early prototypes to limited commercial applications, the importance of the design and integration of solar photovoltaic systems, advancements in energy management and optimization, the use of lightweight materials, and the impact of climate and shading factors on performance. The review concludes by outlining directions for future research on the advancement of energy management systems, with particular emphasis on optimizing solar energy input, battery efficiency, and economic viability. Furthermore, it is recommended to investigate materials that achieve an optimal balance between durability, cost-effectiveness, and photovoltaic performance, as well as to develop adaptive solar capture designs tailored to diverse vehicle platforms.